Impact of Soil Health Card on Urea Fertilizer Usage and Crop Yield in Haryana - Ohlan, Ramphul; Ohlan, Anshu; Singh, Rajbir (Indian Journal of Extension Education, 2025)
Soil health is crucial for sustaining agricultural productivity. This study evaluates the impact of the Soil Health Card (SHC) scheme on fertilizer usage and crop yield in Haryana. Using primary data obtained from farm-level survey conducted utilizing a pre-tested semi-structured schedule in 2024–25, the research compares urea application and crop productivity between SHC adopters and non-adopters. The impact of SHC adoption on urea usage and yield varies across crops. The findings indicate that while SHC-adopting farmers apply urea at levels below conventional practices, they still exceed recommended doses. SHC adoption leads to a statistically significant reduction in urea usage, without compromising crop yields. An economic analysis reveals that paddy and wheat farmers benefit from both cost savings and increased yield. The study underscores the potential of SHC in promoting balanced fertilizer usage while maintaining crop yield. The novel findings support the need for implementation of tailored nutrient management strategies to safeguard soil health.